Increase Global Competition Through Managing the Business and Partnership Patterns - Junaedi, I Wayan Ruspendi (LPPM IAKN Tarutung, 2022)
Attitude of running a business characterized by long-term relationships, a high-level cooperation, mutual trust, where suppliers and customers trade with each other to achieve common business goals. The problem formulation is how partnership patterns in order to increase global competition? The purpose of the research is to find out the pattern of partnerships in order to increase global competition. State of the art (literature study) used is a partnership, pattern and global competition and Increase. The research method used is qualitative research. Data collection using in-depth interviews and documentation. The conclusion is as follows. There are four patterns of partnership: (1). Plasma-Core: is a partnership relationship between micro, small medium enterprises (as plasma) and large enterprises (as the core) of fostering and developing small businesses. (2). General trading: A partnership between a small business with a medium-sized business or large enterprise, where a medium or large business markets the production of a small business, or a small business supplies the needs needed by a medium-sized business or large partner business. (3). Franchising: is a cooperation in which one party is granted the right to exercise the right of intektual wealth, discovery, business cash characteristics such as licenses, trademarks, and distribution channels of his company to the franchisee with the help of management guidance. (4). Agency: is a partnership relationship in which a small business is given special rights to market medium-sized business goods and services or large business partners. (5). Operational cooperation: A pattern of business relationships run by a group of partners with a partner company.